1984
DOI: 10.1300/j018v02n04_04
|View full text |Cite
|
Sign up to set email alerts
|

Group Life Review and Denial of Death

Abstract: In order to assess the utility of structured reminiscing with the elderly a series of five Life Review Workshops (LRW) were offered. Sixty-three seniors participated in the treatment or no-treatment conditions and were administered four attitude measures pre- and post-treatment. Workshop participants also filled out a Workshop Evaluation Form. Analyses showed that the treatment group significantly decreased in denial of death (t = 2.66, p = less than .01) while the control group did not. There were also modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…As initially proposed by Butler (1963), work has also shown that reviewing one's life, as part of a reminiscence group, can help older adults to prepare for death by alleviating fears and increasing death acceptance (e.g., Fishman 1992;Georgemiller and Maloney 1984). At the same time, there are many studies showing that reminiscence groups are not necessarily beneficial, or at least not any more so than a control group or comparison therapeutic technique (e.g., Engels and Vermey 1997;Richeson and Thorson 2002).…”
Section: Introductionmentioning
confidence: 99%
“…As initially proposed by Butler (1963), work has also shown that reviewing one's life, as part of a reminiscence group, can help older adults to prepare for death by alleviating fears and increasing death acceptance (e.g., Fishman 1992;Georgemiller and Maloney 1984). At the same time, there are many studies showing that reminiscence groups are not necessarily beneficial, or at least not any more so than a control group or comparison therapeutic technique (e.g., Engels and Vermey 1997;Richeson and Thorson 2002).…”
Section: Introductionmentioning
confidence: 99%